Qualities of an Effective Clinical Teaching Fellow in Medical Education—A Mixed‐Methods Study - Rocco Sheldon; Andrew Gan; Thomas Fleck; Richard Phillips; Elizabeth Peterknecht (The Clinical Teacher, 2026)
ABSTRACT Introduction Clinical teaching fellows (CTFs) are an increasingly important part of undergraduate medical education in the United Kingdom. Despite their valuable and uniquely multifaceted role, research investigating the qualities that make an effective CTF is limited. This study aimed to identify and compare the views of stakeholder groups regarding the most important qualities of CTFs. Methods We conducted a single‐centre mixed‐methods study at a large UK teaching hospital. An online questionnaire was distributed to clinical medical students (years 3–5), CTFs, administrative staff and faculty. Data were collected via Likert scales, asking respondents to rank qualities and teaching experiences and free‐text responses. Results Quantitative analysis ( n = 43) identified friendliness, being knowledgeable and an engaging teaching style as the most valued qualities. Prior experience of conducting bedside teaching and small‐group tutorials was prioritised, with postgraduate teaching qualifications and specialist knowledge ranked as least important. Medical students valued professionalism and teamwork significantly less than other groups ( p < 0.05). Qualitative thematic analysis revealed students prioritised a supporting learning environment and practical clinical tips. Conversely, administrative staff, faculty and CTFs valued collaborative teamwork and organisational reliability. Reflecting these differences, 29 (67.4%) respondents agreed with our hypothesis that disparities exist between stakeholder groups in the qualities/experiences they value most. Conclusions This study highlights commonalities and differences regarding the interpersonal skills and teaching experiences that are central to effective CTFs. These findings have important implications for recruitment, training and professional development of CTFs, ensuring alignment with the needs of stakeholders and addressing perceived disparities between groups.